Pengaruh Dosis Berbagai Jenis Pupuk Organik Terhadap Pertumbuhan Dan Hasil Tanaman Tomat (Lycopersicum esculentum ) Pada Tanah Podsolik Merah Kuning (PMK) Rokan Hilir - Meli Roslianti; Susanti, Sari; Irwansyah, Chusrin; Nila Wati, Sisi (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2025)
Tomatoes are multipurpose vegetables, in addition to being used as vegetables, they can also be used as raw materials for food processing. Red Yellow Podsolic (RYP)) soil which is widely found in the Rokan Hilir area, has a relatively low fertility level and tends to be acidic. Therefore, choosing the right type and dose of organic fertilizer is very important to improve soil quality and support the growth of tomato plants. The purpose of this study was to obtain the best dose of manure for the growth and yield of tomato plants on Red Yellow Podsolic (RYP) soil. This study used a completely randomized design (CRD) with 2 factors. The first factor is the type of organic fertilizer (P), namely cow manure and goat manure. The second factor is the dose of organic fertilizer (D) consisting of 500 g/plant, 1000 g/plant, 1500 g/plant and 2000 g/plant. The observation data were explained statistically by the analysis of variance (F test). The results showed that the provision of cow manure had a significant effect on flowering age, harvest age and root volume. The administration of a fertilizer dose of 2000 g/plant gave a significant effect on the observation of plant height, root length, and root volume. The administration of goat manure had a significant effect on the observation of the number of fruits per plant and the weight of fruits per plant.